PEMBENTUKAN KARAKTER SISWA MELALUI PENANAMAN NILAI-NILAI MULTIKULTURAL DI SMP NEGERI 02 TASIK PUTRI PUYU - Karmila, Karmila; Chanifudin, Chanifudin (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research focuses on developing the character of students at SMP Negeri 02 Tasik Putri Puyu through the cultivation of multicultural values. The purpose of this study is to identify multicultural values instilled in students, know the process of character development through the cultivation of multicultural values, and to find out the elements that support and hinder character development. To collect data from students and teachers in schools, this study used a qualitative approach with interview, observation, and documentation methods. The results showed that the school has successfully instilled values such as tolerance and democracy among the students. However, there are also factors that hinder the adoption of multicultural values, such as parents' demands for additional religious education. This research contributes to the development of character building in schools and provides insight into the importance of multicultural education in promoting tolerance, inclusivity, humanity, and justice. The research suggests solutions to address challenges in cultivating multicultural values, including continuous reinforcement by teachers, encouraging students to apply these values in school and community settings, and promoting equal treatment among students